Asphalt Concrete Production Technology Using Oil Sludge from Zhaik Munay LLP - Satayeva, Sapura Sanievna; Burakhta, Vera Alekseevna; Urazova, Aliya Frunzeevna; Nazarova, Dauriya Sagindykovna; Khamzina, Bayan Elemesovna; Begaliyeva, Raikhan Sabitovna; Shinguzhieva, Altynay Bakytzhanovna; Satybayeva, Nurgul Artigalievna; Yerzhanova, Zhadyra Toigalievna; Murzagaliyeva, Alma Askarovna (Journal of Engineering and Technological Sciences, 2024)
Oil sludge exhibits a compositional similarity to bitumen, a pivotal constituent in asphalt concrete mixtures. This similarity underscores the potential applicability of oil waste in the production of asphalt concrete, serving not only as an organic binder to fortify indigenous soils but also as a binding agent for the fabrication of organomineral mixtures. The incorporation of oil sludge in road construction endeavors holds promise for the conservation of natural resources, the amelioration of the environmental landscape, and a concurrent reduction in the cost of construction materials. The focus of this study encompasses a comprehensive examination of the physical and mechanical properties pertaining to asphalt concrete of Grade I, Type B. To enhance the performance attributes of asphalt concrete, an additive in the form of oil sludge sourced from ZhaikMunay LLP (Uralsk) was introduced. Various proportions of oil sludge, namely 5%, 10%, and 15%, were incorporated into the asphalt concrete mixture. The utilization of 5% oil sludge elicited negligible alterations in the properties of the asphalt concrete. However, with a 15% addition of oil sludge, discernible reductions were observed in maximum compressive efficiency (0.03% by volume) and shear resistance, indicated by the internal friction coefficient efficiency (0.01% by volume).